PENGARUH MODEL PEMBELAJARAN STUDENT TEAM ACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR PADA MATA PELAJARAN IPS - Amdriyani, Amdriyani; Baisa, Hidayah; Nawawi, Kholil (Program Studi PGMI, 2018)
This study aims to find out the process of applying the Student Team Achievement Division learning model to the learning outcomes of the 3rd grade students in the social studies subjects at SDIT Al-Madinah Cibinong, and to know the effect of the Student Team Achievement Division learning model on the students' SDIT Al-Madinah Cibinong.The approach used in this research is quantitative research with the type of quasi-experimental research, in this study the selection of samples on experimental quasi type Non Equivalent Control Group Design is not done random sample selection but deliberately selected by the researchers ie with each sample experiment class 28 students and control class 28 students. Instruments used in this research are: test and documentation.The results showed that there was a significant effect of IPS students' learning outcomes in third grade between experimental group by applying Student Team Achievement Division and control group with conventional learning. This is evidenced from the t-test at a significant level of 5% of 2.01 while a significant level of 1% of 2.68 and t yield of 9,144 then can be written 2.01 <9,144> 2.68.So the application of learning model Student Team Achievement Division can influence student learning outcomes on IPS subjects are said to be effective and there are significant changes or improvements. Student Team Achievement Division learning model can be one alternative learning model that can be applied in the learning process.